The role of dalbavancin in the multi-disciplinary management of wound infections in orthopaedic surgery. (3rd April 2018) - Arena, Fabio; Romanini, Emilio; Rosi, Elia; Salomone, Carlo; Tucci, Gabriele; Pempinello, Ciro; Fantoni, Massimo
Abstract : Antimicrobial resistance is continuously increasing among bacterial clinical isolates (especially methicillin resistance in Staphylococcus aureus, MRSA), negatively impacting on outcomes of patients with Surgical Site Infections (SSIs). A multi-disciplinary team work is essential for SSIs prevention and for the choice of antibiotic therapy of orthopaedic SSIs. In particular, an Antibiotic Stewardship (AS) approach is recommended for preserving the activity of old and new antimicrobials. Dalbavancin is a novel antimicrobial agent, belonging to the lipoglycopeptides family, recently approved by FDA for the treatment of ABSSSIs (Acute Bacterial Skin and Skin Structure Infections) and can be considered as a candidate for the treatment of orthopaedic superficial SSIs. An antimicrobial activity directed against MRSA and other multi-resistant Gram-positive pathogens, a bactericidal effect and an extremely extended half-life are among key features of this drug. Dalbavancin gives to clinicians the option to provide an intravenous antimicrobial agent shown to be as effective as conventional therapies, without requiring prolonged admission into the hospital, drastically reducing the length of hospital stay (without reducing the treatment compliance) and total cost per patient. In this paper, we analyze general, microbiological and pharmacological features of dalbavancin, aiming at supporting clinicians while positioning this drug in the context of orthopaedic SSIs.